Des Jardins, Women And The Historical Enterprise In America - Gender, Race, And The Politics Of Memory, 1800-1945 - Baker, Carrie (Teaching History: A Journal of Methods, 2005)
Julie Des Jardins’ text is a rich resource for a range of courses, including historiography, women’s history, African-American history, and social and cultural history courses. Des Jardins, an Assistant Professor of History at City University of New York, Baruch College, has written an excellent account of how history has been told in the United States, paying special attention to the "politics of memory"- how the social location of those telling history has shaped their results. Between the late nineteenth century and World War II, the growing professionalization of the study of history within academic institutions resulted in the privileging of political, economic, and military history written by men and based upon a "scientific" inquiry into official legal and governmental documents.